Investigations of photoresponse signals of LT-GaAs photodetector - Białous, Małgorzata; Świtkowski, Krzysztof; Kozanecka-Szmigiel, Anna; Wierzbicki, Michał; Pura, Bronisław (Oficyna Wydawnicza Politechniki Wrocławskiej, 2009)
In this paper, we demonstrate our electro-optic sampling system constructed for characterization of high-speed photodetectors based on low-temperature-grown GaAs (LT-GaAs). Changes in the shape of electrical signals for different optical powers, voltage biases and positions of a probe beam have been shown. The obtained photoresponse of the investigated photodetector exhibits 0.9 ps (full width at half maximum).
Optica Applicata, Vol. 39, 2009, nr 1, s. 161-167
Keywords: optyka; electro-optic sampling; ultrafast photodetectors; low-temperature-grown GaAs (LT-GaAs)